Electron trapping & blocking effect enabled by MXene/TiO2 intermediate layer for charge regulation of triboelectric nanogenerators. (July 2022) - Chen, Xiaoping; Liu, Yina; Sun, Yi; Zhao, Tianshi; Zhao, Chun; Khattab, Tawfik A.; Lim, Eng Gee; Sun, Xuhui; Wen, Zhen
Abstract: As the existence of interfacial electric field, the surface charges of triboelectric nanogenerators (TENGs) would diffuse into air or tribo-material interior, resulting in the charge decay. Therefore, charge regulation from charge storage is crucial in addition to charge generation. In this work, a MXene/TiO2 hybrid film has been prepared through partial oxidation of MXene in a contact-separate mode TENG (MT-TENG) as an intermediate layer between negative tribo-material and bottom electrode. It demonstrates the electric outputs of 128 μC/m 2 in charge density, 73.78 μW/cm 3 and 63.78 μW/g in average power density with an energy conversion efficiency of 34.81%. The surface terminals in MXene nanosheets and the oxygen vacancies in TiO2 nanoparticles provide abundant electron trap sites. Moreover, the energy band bending resulting from the polarization effect of the hybrid film could further hinder the free electrons' drift to the bottom electrode, and consequently prevent the charge recombination. With the synergetic effect of electron storage and polarization, the MT-TENG with an intermediate layer rapidly reaches a charge dynamic equilibrium with a charge density of 80 μC/m 2 . It is expected to provide new insights for material science and structure design from the perspective of charge regulation to improve the output performance of TENGs. Graphical Abstract: The surface charges of triboelectric nanogenerators would diffuse due to the interfacial electric field, causing the charge decay. A MXene/TiO 2 hybrid film has been prepared as an intermediate layer and obtained 128 μC/m 2 in charge density. With the synergetic effect of electron storage and polarization, a charge dynamic equilibrium can be achieved with a charge density of 80 μC/m 2 . ga1 Highlights: The MT-TENG obtained 224 V in open-circuit voltage and 128 μC/m 2 in charge density with a 5-fold enhancement. The average power density of MT-TENG could reach 73.78 μW cm −3 and 63.78 μW g −1 with an energy conversion efficiency of 34.81%. A charge recombination model was constructed. The charge density of MT-TENG could reach saturated 245 μC/m 2 initially, and remain at 80 μC/m 2 with dynamic equilibrium.